2004
DOI: 10.1139/l03-072
|View full text |Cite
|
Sign up to set email alerts
|

A spectral density approach for modelling continuous vertical forces on pedestrian structures due to walking

Abstract: A limitation of existing walking models used for vibration serviceability assessment of structures carrying pedestrians is that they are typically based on direct measurements of single footfalls replicated at precise intervals. This assumption of 'perfect periodicity' allows walking forces to be modelled as a Fourier series of sine waves having frequencies of the walking pace and its integer multiples. The true imperfection and randomness in walking is currently not taken into account even in more advanced dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
110
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 16 publications
1
110
1
Order By: Relevance
“…A critical review of the different approaches for the estimate of the dynamic response in such a loading condition can be found in [3]. They may be classified into three categories: Monte Carlo simulations, simplified procedures ( [4]- [7]) and spectral approach ( [8], [9]). Monte Carlo simulations may be very time consuming and not practical from the usual design of footbridges.…”
Section: Introductionmentioning
confidence: 99%
“…A critical review of the different approaches for the estimate of the dynamic response in such a loading condition can be found in [3]. They may be classified into three categories: Monte Carlo simulations, simplified procedures ( [4]- [7]) and spectral approach ( [8], [9]). Monte Carlo simulations may be very time consuming and not practical from the usual design of footbridges.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the human-induced force is weighted by the mode shape  n in order to take into account that the force moves across the footbridge and it has a limited duration. The walking force F(t) is represented through the pedestrian load model proposed by [25] and based on the results obtained from [27]. By analyzing walking force time-histories measured on a treadmill, [27] found that human-induced walking force is not periodic, but rather it is a narrow band random process, meaning that there is a leaking of energy around the main harmonics in the force spectrum.…”
Section: Simulation Model IImentioning
confidence: 99%
“…The walking force F(t) is represented through the pedestrian load model proposed by [25] and based on the results obtained from [27]. By analyzing walking force time-histories measured on a treadmill, [27] found that human-induced walking force is not periodic, but rather it is a narrow band random process, meaning that there is a leaking of energy around the main harmonics in the force spectrum. Based on the results provided from Brownjohn [27], Živa-nović [25] developed a multi-harmonic force model for the calculation of the multi-mode structural response to a single person walking across a footbridge.…”
Section: Simulation Model IImentioning
confidence: 99%
See 2 more Smart Citations